Efektivitas Cuka Kayu Terhadap Ulat Spodoptera Litura Pada Sawi - Subagiya Subagiya; Retno Wijayanti; Ato Sulistyo; Aulia Kharisma Putri (Universitas Sebelas Maret, 2024)
Wood vinegar is a liquid made from steam cooled wood smoke in the sublimation process. Recently, this material is known to be used as a biopesticide, so it does not have side effects that are harmful to the environment, especially for non-target insects. Ambarwati et al (2013) reported that wood vinegar can control cabbage heartworm (Crocidolomia pavonana) and has an effect in accelerating its life cycle. In addition, wood vinegar can also increase the weight of Edamame soybeans almost twice (Ramli et al, 2020) According to Sri Hartati et al (2013) wood vinegar is also able to inhibit the growth of conidium up to 76%. Mustard greens are vegetables that have good commercial value, but the production is fluctuating. One of the factors that influence the fluctuation of mustard greens production is the presence of Spodoptera litura caterpillars. The development of botanical pesticide is needed to substitute chemical pesticide. This research purposed to obtain an effective concentration of wood vinegar and an appropriate application method to control S. litura caterpillars. This research was conducted in the Laboratory of Plant Pest and Diseases Faculty of Agriculture, Sebelas Maret University (UNS) and in Satriyan, Ngrundul, Kebonarum, Klaten starting from May until August 2020. This study was conducted using a completely randomized experimental design (CRD) with two factors. First factor is concentration of wood vinegar from rice husk (0%, 2%, 4%, 8%, dan 16%) and second factor is application method (leaf dipping method and larvae spraying method). The result showed that wood vinegar with various concentrations tested has no effective effect on S. litura and application methods that used have no different effect.